PENGGUNAAN BAHAN BEKAS KEMASAN DALAM PEMBELAJARAN PADA ANAK USIA DINI - Rara Siti Aisah; Kristiana Maryani; Isti Rusdiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of recycled packaging materials in the learning process for 5–6-year-old children at the Pembina Pandeglang Public Kindergarten. This study employs a qualitative research method with a descriptive approach, utilizing data collection techniques such as observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers at TK Negeri Pembina Pandeglang utilize various recycled packaging materials easily found in the surrounding environment, such as cardboard, straws, scrap paper, and plastic bottle caps as learning media in core activities. Every day, teachers prepare learning activities that involve the use of recycled packaging materials. The use of recycled packaging materials in learning enhances creativity and makes children more active and enthusiastic during the learning process. The conclusion of this study indicates that teachers at TK Negeri Pembina Pandeglang have utilized recycled packaging materials as learning media tailored to their lesson plans, thereby creating creative, enjoyable, economical, and environmentally friendly learning experiences for young children. Keywords: Recycled Packaging Materials, Learning, Early Childhood